PENGARUH MEREK, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU LOKAL VENTELA PADA MAHASISWA/I UNIVERSITAS TEKNOLOGI SUMBAWA - Tirta K. Nangi; Abdul Salam (Jurnal Nusa Manajemen, 2026)
This study aims to examine the influence of: (1) brand on purchasing decisions, (2) price on purchasing decisions, and (3) product quality on purchasing decisions. The analytical model used in this study includes instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The analytical tool applied is SPSS. The data used are primary data, with the sampling technique being purposive sampling. The results of this study indicate that: (1) Brand has a significant influence on purchasing decisions, with a t-value of 2.600 greater than the t-table value of 1.984 and a significance value of 0.011 less than 0.05. (2) Price has a significant influence on purchasing decisions, with a t-value of 6.607 greater than the t-table value of 1.984 and a significance value of 0.001 less than 0.05. (3) Product quality has a significant influence on purchasing decisions, with a t-value of 3.938 greater than the t-table value of 1.984 and a significance value of 0.001 less than 0.05.